Fifteen year history of a huge ovarian serous cystadenoma in association with uterovaginal prolapse - Rana, Ashma; Gurung, Geeta; Ojha, Neeva; Amatya, Sapana; Poudel, Sandesh; Sharma, Savana; Agarwal, Varsha; Deo, Anju; Bhandari, Binay R (Nepal Journal of Obstetrics and Gynaecology, 2014)
A huge ovarian cyst, twice tapped and existing for 15 year, longest duration ever reported in literature and for the last seven years complicated by uterovaginal prolapse is reported here to give an idea about the reproductive morbidity status of socially deprived or underprivileged Nepalese woman in rural community. Abdomino-vaginal surgical approach was combined to drain 16 liters of fluid from the ovarian cyst and excise the tumor capsule by initiating hysterectomy abdominally including the steps up to the ligation of uterine artery thereafter completing the procedure vaginally by taking over the cardinal ligaments, thus facilitating delivery of uterus with its appendages with pelvic floor repair for third degree uterovaginal prolapse. DOI: http://dx.doi.org/10.3126/njog.v3i2.10833 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 51-53